Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/hec.3828
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight on labor market outcomes: An application of genetic instrumental variables

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 54 publications
5
48
0
Order By: Relevance
“…47,48 These findings raise questions about whether height and BMI have causal effects on socioeconomic outcomes later in life. [49][50][51] However, larger studies of related individuals with information on socioeconomic outcomes, such as income and occupation later in life are required to provide definitive evidence about the consequences of height and BMI later in life.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 These findings raise questions about whether height and BMI have causal effects on socioeconomic outcomes later in life. [49][50][51] However, larger studies of related individuals with information on socioeconomic outcomes, such as income and occupation later in life are required to provide definitive evidence about the consequences of height and BMI later in life.…”
Section: Discussionmentioning
confidence: 99%
“…We found that some SNPs are related to obesity-related illnesses like type 2 diabetes and high blood pressure. As in Böckerman et al (2019) we assume that the associations with obesity-related conditions occur because of the SNPs' association with high BMI and WHR, but we cannot definitely rule out other pathways. In a second check, we used the MR-Egger method (Bowden et al, 2015) to test for pleiotropy.…”
Section: Pleiotropymentioning
confidence: 98%
“…However, a potential concern with this approach is that unobserved characteristics may be correlated with both a person's own BMI and their relative's BMI, for example when they live in the same household (Böckerman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MR has been used recently to understand the mechanism of relationship of high BMI and disadvantage of social-economic status, such as low income: Tyrrell et al 28 used highly self-selected UK Biobank data for their analysis, where income is reported at the household level, and Böckerman et al 29 used a small sample for their analysis, which severely limits the power of that study; we refer the reader to these articles for a justification for the existence of a linear effect of BMI on income. We apply the methods introduced above to the larger and more representative UKHLS sample data to estimate the causal effect of BMI on personal income.…”
Section: Analysis Using Ukhls Datamentioning
confidence: 99%